Association Between Carbapenem Resistance and Mortality Among Adult, Hospitalized Patients With Serious Infections Due to Enterobacteriaceae: Results of a Systematic Literature Review and Meta-analysis. (28th June 2018) - Martin, Amber; Fahrbach, Kyle; Zhao, Qi; Lodise, Thomas
Abstract: This study quantified mortality associated with serious infections caused by carbapenem-resistant (CRE) and carbapenem-susceptible Enterobacteriaceae (CSE). A systematic literature review was conducted, evaluating outcomes in hospitalized patients with CRE infections from a blood, urinary, pulmonary, or intra-abdominal source. A meta-analysis (MA) calculating odds ratios (ORs) for mortality was performed. Twenty-two studies met the criteria for inclusion in the MA: 12 included mortality data for CRE vs CSE populations. Compared with CSE, CRE was associated with a significantly higher risk of overall mortality (OR, 3.39; 95% confidence interval [CI], 2.35–4.89), as was monotherapy (vs combination therapy) treatment of patients with CRE infections (OR, 2.19; 95% CI, 1.00–4.80). These results document the increased mortality associated with serious CRE infections compared with CSE infections among hospitalized adults. It will be important to reevaluate the mortality in CRE and CSE populations, especially among patients who receive early appropriate therapy, as new antibiotics become available.